The Ink of Melancholy : Faulkner's Novels from The Sound and the Fury to Light in August - Bleikasten, Andre (Book collections on Project MUSE., 2016)
Ink of Melancholy re-examines and re-evaluates William Faulkner's work from the late 1920s to the early 1940s, one of his most creative periods. Rather than approach Faulkner's fiction through a prefabricated grid, AndrE Bleikasten concentrates on the texts themselves'on the motivations and circumstances of their composition, on the rich array of their themes, structures, textures, points of emphasis and repetition, as well as their rifts and gaps'while drawing on the resources of philosophy, psychoanalysis, anthropology. Brilliant in its thought and argument, Ink of Melancholy is one of the most insightful and stimulating studies of Faulkner's work.